2015
DOI: 10.1245/s10434-015-4571-7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Neutrophil-to-Lymphocyte Ratio is a Better Prognostic Serum Biomarker than Platelet-to-Lymphocyte Ratio in Patients Undergoing Resection for Nonmetastatic Colorectal Cancer

Abstract: High preoperative NLR in this series was shown to be a negative independent prognostic factor in patients undergoing surgical resection for nonmetastatic CRC. The prognostic utility of this serum biomarker may help to guide use of adjuvant therapies and patient counselling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 26 publications
1
77
0
Order By: Relevance
“…Therefore, different statistical methods may obtain different thresholds. However, the method used by the present study was based on R, which has been reliably used by other studies (15,51,52). To conclude, the present study revealed that the combination of the CRP/Alb ratio and NLR represents a potential inflammation-based prognostic marker.…”
Section: Univariate Analysismentioning
confidence: 60%
“…Therefore, different statistical methods may obtain different thresholds. However, the method used by the present study was based on R, which has been reliably used by other studies (15,51,52). To conclude, the present study revealed that the combination of the CRP/Alb ratio and NLR represents a potential inflammation-based prognostic marker.…”
Section: Univariate Analysismentioning
confidence: 60%
“…Similarly, Ishizuka et al [40] reported a higher frequency of nodal involvement in patients with elevated NLR and platelet counts. Other investigators have reported an association between high NLR and colorectal tumour size [41], poor differentiation [4] and mucinous type [42]. In contrast, only a couple of investigators failed to show any association between NLR and clinicopathological features or Dukes staging [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…None of the clinical factors used in known [12][13][14][16][17][18][19][20][21][22] In addition, we did not validate neutrophil-to-lymphocyte ratio above 5 as associated with outcomes, although this has been shown in separate series. 31,32 Measurement of HV CTCs preoperatively by central venous catheterization is feasible but invasive and impractical for a single blood draw. We showed that features more readily measurable preoperatively are associated with HV CTCs.…”
Section: Discussionmentioning
confidence: 99%